Impact of Drought on Growth, Nodulation and Yield in Some Soybean [Glycine max (L.) Merrill] Genotypes - Peter B. S. Gama; James Ochomiyang Wilson (Emerging Issues in Agricultural Sciences Vol. 9, 2023)
Soybean [Glycine max (L.) Merrill] is an important grain legume as well as a potential bio-resource crop (source of vegetable oil). However, drought is one of the environmental stress that affects not only crop yield and growth but also tends to influence presence of native Rhizobium, rooting and root nodulation in legumes such as soybean. The main objectives of this study was to screen the presence of native Rhizobium in soils of Juba and assess the impact of drought on rooting ability, nodulation potential and yield of eighteen (18) soybean genotypes. The results showed that soybean plants that grew under drought produced the highest mean root length of 44.33 cm which were significantly longer than 33.17 cm highest mean root length in the normal treatment (non-drought). Soybean plants that were subjected to drought stress produced the highest number of nodules of 4.67 which was significantly lower than the average number of nodules in the normal treatment (non-drought). It was, therefore, concluded that the root characteristics, nodulation potential and seed yield of soybean was affected by limited water supply. It was also noted that native Rhizobium was present in soils of Juba but it failed to initiate nodulation in some soybean accession. There was significant reduction of seed (grain) yield with accession TGx 2006-3F having the highest seed yield and TGx 1448-3E scoring the lowest. Harvest index (HI %) was comparatively higher in TGx 1485-D and TGx 2010-3F. It is therefore recommended that soybean plants should be supplied with optimum water supply for proper nodulation, growth and yield. Consequently, optimal water supply for soybean growing in pots should be studied for better irrigation management and optimal performance of the plant. For further research, it was suggested that it is of particular importance to inoculate soybean seeds before planting in order to enhance nodulation for improvement of soil fertility through biological nitrogen fixation (BNF).